Evaluation of the Effects of Intravenous and Percutaneous Low Level Laser Therapy in the Management of Shoulder Myofascial Pain Syndrome - Momenzadeh, Sirous; Akhyani, Vahid; Razaghi, Zahra; Ebadifar, Asghar; Abbasi, Mohammadzaki (Journal of Lasers in Medical Sciences, 2016)
Introduction: Myofascial pain syndrome (MPS) treatment is challenging with a high recurrence rate and still lacks a clear treatment frame. Therefore research on new, more efficient and long lasting effect treatment modalities is necessary. This study looked at the effects of intravenous laser therapy (IVL) and percutaneous low level laser (PLLL) in the management of shoulder MPS. Methods: In this randomized controlled trial, 30 patients fulfilling inclusion criteria were randomly equally allocated to 3 groups, control, IVL and PLLL. Control group received 12 sessions of placebo low level laser, IVL group received 12 sessions of IVL therapy, and PLLL group received 12 sessions of PLLL therapy. All patients were trained for better body posture, body mechanics, gentle massage of trigger points, stretching exercises of affected muscle (trapezius), and received 10 mg of oral nortriptyline regimen every night for 3 months. Outcomes included pain severity, functional disability, and quality of life. Patients were assessed using Numeric Rating Scale (NRS), Pain Disability Index (PDI), and Short Form Health Survey (SF-12). Data collected were analyzed using analysis of variance (ANOVA), Mann-Whitney and t tests. Results: The mean of PDI and maximum pain intensity during day and night significantly reduced in both PLLL and IVL groups compared to control group. Although pain severity and PDI reduction was more pronounced in IVL group compared to PLLL group, the differences were not statistically significant. Also, quality of life statistically significantly improved in both IVL and PLLL groups compared to control group was more, and although higher in IVL group, the difference was not statistically significant when compared to PLLL group. No side effects were observed in the intervention groups. Conclusion: Intravenous laser and PLLL therapy had a positive effect on pain severity and PDI reduction, and quality of life in this study. Also no adverse event was recorded. Thus, intravenous lasers and PLLL therapy seem to be effective complementary modalities in managing patients with shoulder MPS.